Castable refractory and molten steel ladle using same
By using strontium aluminate binder and aluminate binder that controls CaO content, the problem that the aluminate binder is prone to form low molten substances at high temperatures is solved, the thermal strength and corrosion resistance of the refractory material are improved, and the service life is extended.
Patent Information
- Application Number
- JP2020173973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-10-15
AI Technical Summary
The existing binding agents containing CaO in aluminate are prone to form low molten substances at high temperatures, resulting in reduced thermal strength and chemical erosion of the refractory materials containing CaO in aluminate, and prone to cracking.
Strontium-containing aluminate is used instead of aluminate binding agent, and a carbon-containing refractory material is used to control the CaO content below 0.3%, avoid the formation of low melts, and suppress cracks caused by thermal expansion through reactions.
It improves the high-temperature thermal strength and corrosion resistance of refractory materials, reduces crack formation and extends service life.
Smart Images

Figure 0007626365000001 
Figure 0007626365000002 
Figure 0007626365000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a castable refractory material for use in a steelworks and a molten steel ladle using the same. [Background technology]
[0002] In recent years, the proportion of castable refractories among all refractories used in steelworks has been increasing. In particular, castable refractories, which are applied by mixing raw materials with water in steelworks, are widely used as refractory linings for molten steel ladles used in secondary refining at the steelmaking stage.
[0003] Damage to refractory linings of molten steel ladles can be caused by spalling due to thermal shock or slag penetration, and erosion by slag. Most castable refractories contain alumina cement, which contains CaO as a binder, but at high temperatures, the CaO component forms low melting points together with Al2O3, MgO, and SiO2, which reduces hot strength and causes chemical erosion.
[0004] In response to this, Patent Documents 1 and 2 propose a binder for castable refractories containing strontium aluminate such as SrAl2O4, and techniques relating to castable refractories using the binder. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5290125 specification [Patent Document 2] Patent No. 6499464 specification Summary of the Invention [Problem to be solved by the invention]
[0006] However, the binder containing strontium aluminate as disclosed in Patent Documents 1 and 2 has a problem in that when CaO is dissolved in the binder and a large amount is added, low melting points are generated during use.
[0007] An object of the present invention is to solve the above problems and to provide a castable refractory material which is easy to work and does not produce low-melting substances during use, and a molten steel ladle using the same. [Means for solving the problem]
[0008] The inventors have confirmed that SrO-Al2O3-SiO2 and SrO-MgO-Al2O3 minerals do not melt even at 1650°C, and that for castable refractories containing carbon, cracks after heat treatment can be suppressed by using cement containing strontium aluminate instead of alumina cement containing calcium aluminate, and have developed the present invention.
[0009] That is, the present invention relates to a castable refractory containing alumina, carbon and magnesia, or a castable refractory containing alumina, carbon and spinel, characterized in that it contains 7 mass % or more and 20 mass % or less of cement containing strontium aluminate and a dispersant, and the CaO content in the raw materials excluding the dispersant is 0.3 mass % or less.
[0010] In the castable refractory according to the present invention configured as described above, (1) The cement containing strontium aluminate is contained in an amount of 11% by mass or more and 20% by mass or less. (2) The cement containing strontium aluminate is contained in an amount of 11% by mass or more and 14% by mass or less. This is believed to be a more preferable solution.
[0011] The present invention also provides a molten steel ladle, characterized in that the above-mentioned castable refractory is used as a lining refractory material. Effect of the Invention
[0012] According to the castable refractory of the present invention, by using cement containing strontium aluminate instead of alumina cement, the content of CaO derived from cement is reduced, the amount of low melting matter generated by CaO is reduced, and high hot strength and excellent corrosion resistance can be obtained. In addition, by making the amount of CaO in the raw materials excluding the dispersant 0.3 mass% or less, high hot strength can be obtained without deteriorating the corrosion resistance.
[0013] In addition, alumina cement is dissolved in water at temperatures above 1400°C according to the following formula (1): CaAl4O7+4Al2O3→CaAl 12 O 19 (1) The reaction causes volume expansion. Castable refractories that do not contain carbon shrink when sintered at 1400℃ or higher, but in castable refractories that contain carbon, the carbon inhibits sintering, so the linear change rate increases after cooling due to the reaction in formula (1), and cracks may occur in the applied body. If cement that contains strontium aluminate is used instead of alumina cement, the reaction in formula (1) does not occur, so the residual expansion after heat treatment is not greater than necessary, and there is also the effect of preventing cracks from occurring in the applied body.
[0014] Furthermore, in the molten steel ladle according to the present invention, the castable refractory according to the present invention, which is excellent in the above-mentioned corrosion resistance and hot strength, is used as the lining refractory, so that a molten steel ladle with high durability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The castable refractory according to the present invention is a castable refractory containing alumina, carbon and magnesia, or a castable refractory containing alumina, carbon and spinel, characterized in that it contains 7% by mass or more and 20% by mass or less of cement containing strontium aluminate and a dispersant, and the content of CaO in the raw materials excluding the dispersant is 0.3% by mass or less.
[0016] According to the present invention, the cement in the castable refractory material is replaced by a cement containing strontium aluminate instead of alumina cement, so that the amount of low melting substances containing CaO, such as Ca2Al2SiO7 and CaAl2SiO6, which melt at 1600°C or less, is reduced, and instead, SrAl2Si2O8 and Sr, which do not melt even at 1650°C, are produced. 0.92 Mg 0.91 Al 10.09 O 17 etc., improving corrosion resistance and hot strength. In addition, by setting the CaO content to 0.3 mass% or less, the amount of the above low melting substances containing CaO produced is reduced, making it possible to obtain high hot strength without reducing corrosion resistance. Furthermore, because the reaction of formula (1) above does not occur, cracks do not occur after heat treatment.
[0017] The cement containing strontium aluminate is contained in the castable refractory in an amount of 7% by mass or more to 20% by mass, preferably 11% by mass or more to 20% by mass, and more preferably 11% by mass or more to 14% by mass. Here, if the cement containing strontium aluminate is less than 7% by mass, the strength required for form removal cannot be obtained. If the cement containing strontium aluminate exceeds 20% by mass, the workability decreases and the amount of water required for work increases, resulting in an increase in apparent porosity. Furthermore, the CaO content in the raw materials other than the dispersant is 0.3% by mass or less. If the CaO content in the raw materials other than the dispersant exceeds 0.3% by mass, the corrosion resistance and hot strength decrease.
[0018] As raw materials other than cement, alumina, carbon and magnesia, or alumina, carbon and spinel are contained as refractory raw materials. Here, carbon refers to scaly graphite, scaly graphite, earthy graphite, artificial graphite, pitch, carbon black, anthracite, coke, etc. As for cement containing strontium aluminate as a binder, for example, a commercially available product with SrO=17.2 mass%, Al2O3=76.5 mass%, CaO=1.5 mass%, and SiO2=0.1 mass% can be used. As a binder, in addition to cement containing strontium aluminate, alumina sol, silica sol, etc. can be used in combination. In addition, various metals such as metallic silicon, and carbides such as silicon carbide and boron carbide may be contained as antioxidants. Furthermore, silica fume, clay, etc. may be contained as a part of the refractory raw materials as long as it is about 5 mass% or less. In addition to the above raw materials, various dispersants such as polycarboxylic acid-based, polyether-based, polymer-based, and naphthalenesulfonic acid-based dispersants, as well as various other additives commonly used in castable refractories, may be used.
[0019] In the present invention, the content of each of the CaO contents in the raw materials other than the cement containing strontium aluminate and the dispersant is the same as that used in general castable refractories, and the following example is given as an example. First, in a castable refractory containing alumina, carbon, and magnesia, the content of fused alumina or sintered alumina is 39% by mass or more and 85% by mass or less, the content of calcined alumina is 2% by mass or more and 20% by mass or less, the content of carbon is 1% by mass or more and 10% by mass or less, the content of magnesia is 5% by mass or more and 10% by mass or less, and the content of dispersant is 0.05% by mass or more and 2.5% by mass or less. In addition, in a castable refractory containing alumina, carbon, and spinel, the content of alumina is 12% by mass or more and 73% by mass or less, the content of calcined alumina is 2% by mass or more and 20% by mass or less, the content of carbon is 1% by mass or more and 10% by mass or less, the content of spinel is 17% by mass or more and 37% by mass or less, and the content of dispersant is 0.05% by mass or more and 2.5% by mass or less.
[0020] The use of fine particle calcined alumina as part of the alumina aggregate is advantageous when using cement containing strontium aluminate, as this is expected to improve strength one day after construction, particularly in winter when the temperature is low. EXAMPLES
[0021] <Example 1> Table 1 below shows Examples 1 to 7 of the present invention and Comparative Examples 3 and 4 in which cement containing strontium aluminate (hereinafter referred to as strontium cement) is applied to an alumina-magnesia-carbon castable refractory material, as well as Comparative Example 2 in which alumina cement is applied, and Comparative Example 1 in which alumina cement is applied to an alumina-magnesia castable refractory material.
[0022] Inventive Examples 1 to 4 all contain 5 mass% flaky graphite, with Inventive Example 1 being an alumina-magnesia-carbon castable refractory material using 7 mass% strontium cement, Inventive Example 2 being 11 mass% strontium cement, Inventive Example 3 being 14 mass% strontium cement, and Inventive Example 4 being 20 mass% strontium cement. Inventive Examples 5, 6, and 7 all contain 7 mass% strontium cement, with Inventive Example 5 being an alumina-magnesia-carbon castable refractory material using 1 mass% flaky graphite, Inventive Example 6 being 10 mass% flaky graphite, and Inventive Example 7 being 2.5 mass% pitch and 2.5 mass% carbon black.
[0023] Comparative Example 1 is an alumina-magnesia castable refractory using 7% by mass of alumina cement. Comparative Example 2 is an alumina-magnesia-carbon castable refractory using 7% by mass of alumina cement. Comparative Example 3 is an alumina-magnesia-carbon castable refractory using 6% by mass of strontium cement, which is less than the range of the present invention. Comparative Example 4 is an alumina-magnesia-carbon castable refractory using 21% by mass of strontium cement, which is more than the examples of the present invention, and having a CaO content higher than the range of the present invention.
[0024] Each raw material was weighed and mixed in a separate bag of scaly graphite, pitch, and carbon black according to Table 1 so that the total weight was 2.5 kg, and both the powder and liquid were stored overnight in a refrigerator at 5°C. The next day, the mixture was taken out of the refrigerator, and the raw materials other than scaly graphite, pitch, and carbon black were placed in a universal mixer, stirred for 1 minute, and then the liquid was added, stirred for 2 minutes, and then scaly graphite, pitch, and carbon black were added and stirred for another 1 minute. The mixture was then poured into a 40 x 40 x 160 mm mold, vibrated with a table vibrator for 30 seconds, and then stored in a refrigerator at 5°C. After one day, the mixture was taken out of the refrigerator, demolded, and subjected to a bending test using a universal testing machine according to JIS R 2553. If the result of the bending test is 0.8 MPa or more, it is determined that the mixture can be removed from the mold the next day, even in winter.
[0025] Separately, according to Table 1, each raw material was weighed and mixed so that the total weight was 2.5 kg, with only the scaly graphite, pitch, and carbon black in separate bags. The raw materials other than the scaly graphite, pitch, and carbon black were then placed in a universal mixer and stirred for 1 minute, and the liquid was added and stirred for 2 minutes, after which the scaly graphite, pitch, and carbon black were added and stirred for another minute. The mixture was poured into a 30 x 30 x 120 mm mold for the hot bending test, and into a 40 x 40 x 40 mm mold for the slag erosion test. After pouring into the mold, it was vibrated for 30 seconds with a table vibrator. It was then removed from the mold after curing at 20°C for 1 day.
[0026] The 30 x 30 x 120 mm samples were dried at 110°C for 24 hours, and then the samples other than Comparative Example 1 were placed in a silicon carbide container with coke breeze, while the sample of Comparative Example 1 was heat treated in an electric furnace at 1400°C for 3 hours without being placed in a container.They were then placed in an electric furnace controlled at 1400°C with coke breeze and subjected to a hot bending test with a crosshead lowering speed of 0.5 mm / min.
[0027] The 40×40×40 mm sample was dried at 110°C for 24 hours, and then heat-treated at 1650°C for 1 hour in an electric furnace while flowing nitrogen gas. A φ20×15 mm hole was drilled at the top of the sample, and 7 g of reagents adjusted to Fe2O3=0.9 mass%, SiO2=5.0 mass%, Al2O3=13.2 mass%, CaCO3=77.2 mass%, and MgO=3.8 mass% were filled into the hole, and heat-treated again at 1650°C for 1 hour in an electric furnace while flowing nitrogen gas. After cooling, the dimensional change in the diameter of the hole before and after the test was measured to determine the corrosion thickness, which was normalized to 100 for Comparative Example 1 to obtain the corrosion index. The results are shown in Table 1 below.
[0028] [Table 1]
[0029] The results in Table 1 reveal the following. Inventive Examples 1 to 7, the bending strength after curing at 5°C for 1 day was 0.8 MPa or more, and Inventive Examples 2 to 4, which used 11 mass% or more of strontium cement, had higher strength than Comparative Examples 1 and 2, which used 7 mass% alumina cement. Comparative Example 3, which used 6 mass% strontium cement, had a bending strength of less than 0.8 MPa after curing at 5°C for 1 day.
[0030] Comparative Example 2, which used 5 mass% flake graphite and 7 mass% alumina cement, expanded and cracked after heat treatment at 1400°C for 3 hours, making it impossible to evaluate the properties after heat treatment. However, all of Inventive Examples 1 to 7 had smaller linear change rates after heat treatment at 1400°C for 3 hours than Comparative Example 1, which used 7 mass% alumina cement.
[0031] Inventive Examples 1 to 7 all had higher 1,400°C hot bending strength than Comparative Example 1, which used 7 mass% alumina cement. In addition, because the CaO content was low, the corrosion index was the same or lower than Comparative Example 1, and the corrosion resistance was the same or higher.
[0032] In Comparative Example 4, which had a larger amount of strontium cement and a larger CaO content than the examples of the present invention, the corrosion index was larger than that of Comparative Example 1 and the corrosion resistance was inferior due to the large amount of CaO and the large amount of water required for construction, 8.8 mass %.
[0033] <Example 2> Table 2 below shows Examples 11 to 17 of the present invention and Comparative Examples 13 and 14 in which strontium cement was applied to an alumina-spinel-carbon castable refractory, as well as Comparative Example 12 in which alumina cement was applied, and Comparative Example 11 in which alumina cement was applied to an alumina-spinel castable refractory.
[0034] Inventive Examples 11 to 14 all contain 3 mass% flaky graphite, with Inventive Example 11 being an alumina-spinel-carbon castable refractory material using 7 mass% strontium cement, Inventive Example 12 being 11 mass% strontium cement, Inventive Example 13 being 14 mass% strontium cement, and Inventive Example 14 being 20 mass% strontium cement. Inventive Examples 15 to 17 all contain 7 mass% strontium cement, with Inventive Example 15 being an alumina-spinel-carbon castable refractory material using 1 mass% flaky graphite, Inventive Example 16 being 10 mass% flaky graphite, and Inventive Example 17 being 1.5 mass% pitch and 1.5 mass% carbon black.
[0035] Comparative Example 11 is an alumina-spinel castable refractory using 7% by mass of alumina cement. Comparative Example 12 is an alumina-spinel-carbon castable refractory using 7% by mass of alumina cement. Comparative Example 13 is an alumina-spinel-carbon castable refractory using 6% by mass of strontium cement, which is less than the range of the present invention. Comparative Example 14 is an alumina-spinel-carbon castable refractory using 21% by mass of strontium cement, which is more than the examples of the present invention, and having a CaO content greater than the range of the present invention.
[0036] Using each raw material, samples were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2 below.
[0037] [Table 2]
[0038] The results in Table 2 reveal the following. Inventive Examples 11 to 17, the bending strength after curing at 5°C for 1 day was 0.8 MPa or more, and Inventive Examples 12 to 14, which used 11 mass% or more of strontium cement, had higher strength than Comparative Examples 11 and 12, which used 7 mass% alumina cement. Comparative Example 12, which used 6 mass% strontium cement, had a bending strength of less than 0.8 MPa after curing at 5°C for 1 day.
[0039] Comparative Example 12, which contained 3 mass% flake graphite and 7 mass% alumina cement, expanded after heat treatment at 1400°C for 3 hours, and cracks occurred in the applied body. However, all of Inventive Examples 11 to 17 had the same linear change rate as Comparative Example 11, which contained 7 mass% alumina cement, and no cracks occurred.
[0040] Inventive Examples 11 to 17 all had higher 1,400°C hot bending strength than Comparative Example 11, which used 7 mass% alumina cement. In addition, because the CaO content was low, the corrosion index was the same or lower than Comparative Example 11, and the corrosion resistance was the same or higher.
[0041] In Comparative Example 14, which had a larger amount of strontium cement and a larger CaO content than the examples of the present invention, the corrosion index was larger than that of Comparative Example 11 and the corrosion resistance was inferior due to the large amount of CaO and the large amount of water required for construction, 8.5 mass %.
[0042] <Example 3> The alumina-spinel-carbon castable refractory of Example 12 of the present invention was poured into the bottom of a 300-ton molten steel ladle in an amount of 11.5 t. Also, the alumina-magnesia castable refractory of Comparative Example 1 was poured into the bottom of another 300-ton molten steel ladle in an amount of 12 t. In both cases, the alumina-magnesia castable refractory was poured into the steel bath part one day later, and magnesia-carbon bricks were piled in the slag line part. After that, both molten steel ladles were dried and preheated under the same conditions and received molten steel. The amount of application was smaller in Example 12 of the present invention because the bulk density of the alumina-spinel-carbon castable refractory was smaller than that of the alumina-magnesia castable refractory, since the bulk density of graphite is smaller than that of alumina. Comparative Example 1 was repaired after 110 uses, whereas the example of the present invention could be used 132 times.
[0043] [Table 3]
[0044] As is clear from the above examples, the castable refractory according to the present invention has high hot strength and excellent corrosion resistance, and is less likely to crack when applied. Therefore, a molten steel ladle using the castable refractory according to the present invention as a lining refractory has high durability even when used under high heat. [Industrial Applicability]
[0045] The castable refractory according to the present invention is not limited to the above-mentioned examples, and various applications can be added within the scope of the present invention, and the castable refractory can be applied to all castable refractories used in steelworks.
Claims
1. A castable refractory containing alumina, carbon and magnesia, characterized in that it contains 11% by mass or more and 20% by mass or less of cement containing strontium aluminate, and a dispersant, and the content of CaO in the raw materials excluding the dispersant is 0.3% by mass or less.
2. 2. The castable refractory according to claim 1, comprising 11% by mass or more and 14% by mass or less of the cement containing strontium aluminate.
3. A molten steel ladle, comprising the castable refractory according to claim 1 or 2 as a lining refractory material.
Citation Information
Patent Citations
Method of providing throating at corner portion of second floor of twoostoried dwelling house
JP1977090125A
Heat resistant castable blend
JP1981104782A
Castable blend
JP1981104783A
Permanent magnet bonded structure in rotary electric machine
JP1989099464A
Ladle-lining carbon-containing amorphous refractories
JP1992050178A